Axial coil accelerator of plasma ring in the atmospheric pressure air - Korytchenko, K. V.; Bolyukh, V. F.; Rezinkin, O. L.; Burjakovskij, S. G.; Mesenko, O. P. (National Science Center "Kharkov Institute of Physics and Technology", 2019)
An axial coil accelerator for acceleration of plasma formation having intrinsic magnetic field in the atmosphere is designed. A problem of a round plasma formation in the atmospheric pressure air is solved by electrical wire explosion where an initial form of an exploding wire corresponded to a ring. A vortex current into the created plasma ring is inducted by the coil accelerator to generate intrinsic magnetic field of the plasma formation. This process is synchronized with reduction in the magnetic coupling between the plasma formation and the accelerator coil during the acceleration.

Розроблена техніка створення та прискорення плазмового формування з власним магнітним полем в атмосферному середовищі. В основу розробленої техніки покладено формування газоплазмового середовища у вигляді кільця в атмосферному середовищі шляхом електричного вибуху провідника у вигляді кільця, подальшого індукування вихрового струму в газоплазмовому середовищі за допомогою індукційного прискорювача та забезпечення умов для накопичення енергії магнітного поля в плазмовому формуванні шляхом його електродинамічного прискорення, що забезпечує послаблення магнітного зв’язку між плазмовим формуванням та індуктором прискорювача.
Аксіальний індукційний прискорювач плазмового кільця в повітрі за атмосферного тиску
Keywords: magnetic field; axial coil accelerator; electrical energy; atmospheric pressure; current; impulses; магнітне поле; осьова котушка прискорювача; електрична енергія; атмосферний тиск; струм; імпульси